The Legal and Regulatory Framework for Microfinance in Iraq - World Bank Group (Washington, DC, 2015)
Over the past few years, Microfinance Institutions (MFIs) in Iraq have emerged as credible sources of financing for low-income households and entrepreneurs, both underserved by conventional banks. Microfinance services in Iraq, however, are still nascent and far from meeting their full potential. Similar to many countries in the MENA region, MFIs in Iraq were set up as non-governmental organizations (NGOs) supported by a steady influx of donor funding. While these NGOs were initially able to grow through donor support, they are now struggling to meet increasing client demand as donor resources have dwindled, preventing them from making the necessary investments in capital and infrastructure to meet growing client demand. Many countries address this funding challenge by allowing institutions to provide financial services as companies or banks, helping them raise capital, provide new services, and increase their outreach in a sustainable manner. A similar path could be envisioned in Iraq, but is currently obstructed by regulatory hurdles. This diagnostic report aims to present and assess the current microfinance landscape in Iraq, including the legal and regulatory framework, recommend policy improvements to enhance the sustainability and operating environment for MFIs and their clients. This report argues that the current legal and regulatory environment for microfinance in Iraq hinders the growth and sustainability of the sector and furthermore advocates several short and medium term policy recommendations to enhance the overall operating environment for MFIs, the sustainability of the sector, and impact for clients.